A Comprehensive Study on the Synthesis and Characterization of TiO2 Nanoparticles Using Aloe vera Plant Extract and Their Photocatalytic Activity against MB Dye. (28th July 2022) - Srujana, S.; Anjamma, M.; Alimuddin,; Singh, Bharat; Dhakar, Ram C.; Natarajan, Shanthi; Hechhu, Ramana
Abstract : This paper investigates the use of A. vera extract as a natural capping agent for TiO2 nanoparticles as well as a reducing agent for TiO2 nanoparticles. XRD, ultraviolet diffuse reflectance (UV-DRS), Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and energy-dispersive X-ray analysis (EDXA) were used to characterize the material. In their X-ray diffraction patterns, the titanium dioxide nanoparticles were found to have a high degree of crystallinity, indicating that they were synthesized. Infrared (FT-IR) spectra were used to determine the chemical composition of the plant extract. The DRS spectra in the UV-visible range reveal a high absorption peak at 356 nm, which indicates the existence of TiO2 nanoparticles in the sample. Shape of nanoparticles was revealed by SEM and TEM morphological investigations, which revealed their irregular and somewhat spherical nature. Only titanium and oxygen compounds were found in the EDX spectrum, indicating that they were present. This demonstrates that the NPs that were produced are devoid of contaminants. Using the produced nanoparticles as catalyst, we presented a photocatalytic degradation method for the dye methylene blue in this paper. The findings showed that 94 percent of the damage occurred within 120 minutes of being exposed to UV radiation.